In Silico Analysis for Exploring the Potential Inhibitors Against Breast Cancer (MCF7) Using Curcumin Analogue Compounds - Neni Frimayanti; Adel Zamri; Yum Eryanti (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Breast cancer is one of the most problematic diseases in the world. Currently, there are no potential vaccines for the treatment of this disease. Therefore, finding effective compounds, such as curcumin analogs, is crucial to inhibit breast cancer. Forty-five synthesized curcumin analogs were tested on the MCF7 cell line using the MTT assay. It was shown that nine curcumin compounds, Cpd 5, Cpd 9, Cpd 17, Cpd 18, Cpd 21, Cpd 25, Cpd 28, Cpd 32, and Cpd 45, had better inhibitory activities against breast cancer. Furthermore, in silico analysis was developed using 2D and 3D QSAR models with high predictive ability, with an r2 value of 0.834. In addition, based on molecular docking, molecular dynamics, and pharmacophore results, it was shown that these nine compounds had the lowest binding free energy and were also stable during the simulation. The presence of methoxy groups, hydrogen bond donors, and aromatic ring features are the main factors that enhance the biological activity of curcumin analogs. Therefore, these compounds could serve as references for the next stage of drug design.